A Dopamine Sensor Based on Pre-Concentration by Magnetic Nanoparticles. (30th September 2013) - Bagherzadeh, Mojtaba; Ansari, Somayeh; Riahi, Fariborz; Farahbakhsh, Anahita
Abstract : Herein, Fe3 O4 magnetic nanoparticles (MNPs) were synthesized and characterized. Afterward, a magnetic carbon paste electrode (MCPE) was modified with MNPs via casting and drying MNPs on top of the MCPE (MCPE/MNP). Electrochemical behavior of the MCPE/MNP was studied by cyclic voltammetry in the presence of [Fe(CN)6 ] 3−/4− as a redox probe, and surfacep K a of MNPs was evaluated as6.3 ± 0.1 . The behavior of MCPE/MNP towards dopamine (DA) and ascorbic acid (AA) has been investigated by electrochemical methods, and the obtained results showed that the MCPE/MNP has adsorption behavior towards only DA. Based on this behavior, the DA molecules were pre-concentrated on top of the MCPE/MNP and followed with stripping in DA free solution. Subsequent to experimental and instrumental optimization, a calibration curve from5.0 × 10 - 6 to1.0 × 10 - 3  M DA withr 2 = 0.999, DL =7.6 × 10 - 7  M DA, and RSD = 4.6%, was obtained in the presence of1.0 × 10 - 3  M AA. Performance of the MCPE/MNP was successfully tested in a pharmaceutical sample.